2002
DOI: 10.1074/jbc.m208551200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ribosomal Proteins Specific to Higher Eukaryotic Organisms

Abstract: This report describes the identification of a novel protein named PS1D (Genbank TM accession number AJ272345), which is composed of an S1-like RNA-binding domain, a (cysteine)؋3-(histidine) CCCH-zinc finger, and a very basic carboxyl domain. PS1D is expressed as two isoforms, probably resulting from the alternative splicing of mRNA. The long PS1D isoform differs from the short one by the presence of 48 additional amino acids at its amino-terminal extremity. Analysis of PS1D subcellular distribution by cell fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…It codes for a putative S1-like ribosomal protein that, in conjunction with rRNA molecules, make up ribosomal subunits involved in the cellular process of translation. They are also described to be responsible for the stabilization of highly compact rRNA structures by filling the gaps between RNA domains [31]. Our observations that VvFS41 and VvUBP1 are mostly expressed during DS0 and DS2 (Fig.…”
Section: Sultanine Berry Genes Specific To Fruit-set (Ds0) and 2 Weeksupporting
confidence: 54%
“…It codes for a putative S1-like ribosomal protein that, in conjunction with rRNA molecules, make up ribosomal subunits involved in the cellular process of translation. They are also described to be responsible for the stabilization of highly compact rRNA structures by filling the gaps between RNA domains [31]. Our observations that VvFS41 and VvUBP1 are mostly expressed during DS0 and DS2 (Fig.…”
Section: Sultanine Berry Genes Specific To Fruit-set (Ds0) and 2 Weeksupporting
confidence: 54%
“…Pre-mRNA synthesis and splicing are increasingly recognized as occurring in tandem (Saldi et al, 2016), and a possible coordinating role for ZCCHC17 could lead to disruptions in both processes. In addition to ZCCHC17's nuclear role, early work also found that cytoplasmic ZCCHC17 cofractionates with ribosomes (Gueydan et al, 2002). This led some to initially propose that ZCCHC17 was part of the ribosome complex (Gueydan et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…ZCCHC17 is a poorly understood protein that has been shown to interact with transcription factors (Chang et al, 2003;Joo et al, 2010) as well as splicing factors (Lin et al, 2017;Ouyang, 2009). ZCCHC17 contains a zinc-finger (CCHC) domain and a nuclear localization signal, and microscopy has localized ZCCHC17 to the nucleus and nucleolus (Chang et al, 2003;Gueydan et al, 2002;Lin et al, 2017;Ouyang, 2009). Although there is no published experimental study of ZCCHC17 protein in brain tissue, a recent metaanalysis of RNA expression data from six previous gene expression studies of AD brain tissue included ZCCHC17 as one of the top 30 most reliably downregulated genes in AD (Li et al, 2015).…”
Section: Zcchc17 Loss Correlates With Loss Of Synaptic Genes In Admentioning
confidence: 99%
“…4k) when pNO40 was overexpressed in CV1 cells. Upon overexpression, pNO40, a core component of 60S ribosome subunit [Gueydan et al, 2002;Chang et al, 2003], was concentrated in nucleoli ( Fig. 4j) and induced marked SRrp37 nucleolar co-localization (arrows in Fig.…”
Section: Dual Location Of Srrp37 In Nuclear Speckles and Nucleolimentioning
confidence: 97%
“…In general, no specific NoLSs have been described, but likely, a long array of basic amino acid flanked by basic amino acids, RXXR motifs (in which the X is preferably an arginine or leucine), or RGG motifs, may act as NoLS [Quaye et al, 1996;Liu et al, 1997;Das et al, 1998]. Many ribosomal proteins that transit to the nucleolus to be assembled with rRNA contain such a signal for nucleolar localization [Gueydan et al, 2002], and it should be noted that SRrp37 NoLS contains two such motifs (Fig. 2B) that might mediate SRrp37 nucleolar translocation.…”
Section: Characterization Of Srrp37mentioning
confidence: 99%